Exploring Spatio-Temporal Variations in Water and Land Resources and Their Driving Mechanism Based on the Coupling Coordination Model: A Case Study in Western Jilin Province, China - Lujuan Zhang; Guzailinuer Aihemaitijiang; Zihao Wan; Mingtang Li; Jiquan Zhang; Feng Zhang; Chunli Zhao (Agriculture)
Water and land resources (WLR) are the most important basic resources for social and economic development. The effective alignment of WLR is crucial for maximizing resource utilization and promoting sustainable regional development. This study focuses on Western Jilin Province (WJP), China, employing the degree of coupling coordination model, spatial autocorrelation, and the center of gravity transfer model to assess and characterize the spatio-temporal differentiation patterns of water and land resource matching from 2006 to 2020. Five indicators—annual average temperature (AAT), urbanization rate (UR), population density (PD), reclamation rate (RR), and water resource utilization rate (WRUR)—were selected as influencing factors. A Tobit model was constructed to elucidate the driving mechanisms behind the evolution of the WLR coupling coordination degree (CCD) in WJP. The results indicate the following: (1) From a temporal perspective, the coupling coordination degree of WLR in WJP has shown a year-on-year increase from 2006 to 2020, transitioning from a moderate imbalance to intermediate coordination, reflecting a trend of continuous improvement. (2) Regarding spatial distribution, the overall center of gravity of water and land resource coupling coordination remained relatively stable between 2006 and 2020; however, the direction of distribution gradually shifted from the northeast to the southwest and then from the northwest to the southeast. (3) The AAT, PD, and RR from 2006 to 2020 were all statistically significant at p < 0.01. Notably, the RR positively influences the CCD of WLR, whereas the AAT and PD exert a negative impact. In contrast, the UR and WRUR do not significantly affect the CCD of WLR.